Androgens target prohibitin to regulate proliferation of prostate cancer cells. - Gamble, S; Odontiadis, M; Waxman, J; Westbrook, J; Dunn, M; Wait, R; Lam, E; Bevan, C (2004)
Proteins involved in the growth response of prostate cancer cells to androgen were investigated by comparing the proteomes of LNCaP cells treated with vehicle or androgen. Whole-cell lysates were separated by two-dimensional PAGE, and HPLC-MS/MS was used to identify androgen-regulated proteins. Prohibitin, a protein with cell-cycle regulatory activity, was shown to be downregulated by 50% following androgen stimulation. Western blot and reverse transcription-PCR experiments confirmed the result and showed that regulation occurs at the level of transcription. To determine the importance of prohibitin in androgen-stimulated growth, we used transient transfection to overexpress the protein and RNA interference to knock down the protein. Subsequent FACS analysis showed that cells with reduced levels of prohibitin showed a slight but reproducible increase in the percentage of population in cell cycle, while cells with increased prohibitin levels showed a clear reduction in the percentage entering cell cycle, following dihydrotestosterone stimulation, when compared to untransfected controls. Confocal microscopy showed localization of prohibitin in the nucleus as well as the mitochondria of LNCaP cells. It therefore seems that the regulation of prohibitin is a vital part of the cellular growth response to androgen stimulation in LNCaPs and prohibitin may have a nuclear regulatory role in cell-cycle progression.